2018
DOI: 10.1111/cod.12990
|View full text |Cite
|
Sign up to set email alerts
|

Delayed‐type allergy to cobalt—comparison of a flow cytometric lymphocyte proliferation test with patch testing

Abstract: Background The patch test is the standard procedure for diagnosing delayed‐type sensitization. If a patch test is not possible, the flow cytometric lymphocyte proliferation test (LPT), which determines the number and type of cells responding to a specific antigen in vitro, might be considered as an alternative. Objectives Our aim was to establish a flow cytometric LPT for the detection of delayed‐type allergic responses to cobalt, and to determine the correlation between stimulation indices (SIs) in LPT and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The nonheated inactivated autologous serum is indeed an attractive approach to optimizing the LPT; however, the influencing factors in the allergic individuals' autologous serum are still unknown, making, for example, fluctuations of these factors a potential problem. In concordance with previous reports, 14–16,32 we observed the Th cell as the dominant circulating cell type reacting to metals. Detailed analysis of the metal‐reactive Th cells revealed high expression of CD4 and CD45RO.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The nonheated inactivated autologous serum is indeed an attractive approach to optimizing the LPT; however, the influencing factors in the allergic individuals' autologous serum are still unknown, making, for example, fluctuations of these factors a potential problem. In concordance with previous reports, 14–16,32 we observed the Th cell as the dominant circulating cell type reacting to metals. Detailed analysis of the metal‐reactive Th cells revealed high expression of CD4 and CD45RO.…”
Section: Discussionsupporting
confidence: 93%
“…This could indicate that there is indeed a cross‐reactivity on the T‐cell level of the Ni‐ and Co‐reactive patients—however, more studies such as that recently published by Kapp et al 26 are needed. As reported by others, 16 detecting Co‐reactive cells by the LPT was less accurate than detecting Ni‐reactive cells. Whether this is attributable to false‐positive Co patch test 39 or merely an overall lower relative frequency of Co‐specific Th cells needs to be investigated.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…However, recent attempts to better standardize it or to increase its specificity have been published. [40][41][42][43][44] Another controversial issue is preoperative subcutaneous implantation of material probes as a biocompatibility assay. Beecker et al had suggested to use subcutaneous metal implant probes to predict complications following insertion of knee implants.…”
Section: Discussionmentioning
confidence: 99%